THE PREVALENCE OF COLOR VISION DISORDER (CVD) AND CONSANGUINITY IN POPULATION OF DISTRICT KARAK, KHYBER PAKHTUNKHWA (KP), PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
Objectives: To observe the prevalence of color vision disorder (CVD) in district Karak, Khyber Pakhtunkhwa (KP) Pakistan from September 2023 to September 2024.Methodology: During this field work, samples of 555 (300 male and 255 female) individuals were collected from surrounding locations, i.e. Karak city, Metha khel, Landiwa, Thth-e-Nasrati, Gurguri, Latamber, Banda Dawood Shah and Shagi Banda. The data were collected via a predesigned questionnaire printed in Urdu and English, and the history of consanguinity of parents was also recorded.Results: We used Ishihara test, City University test (CUT) and Farnsworth D-15 to identify color blind people, revealed that 28 people (5.04%) were color blind. Out of these, 19(67.85%) were males and 9(32.14%) were females. Among these, 28 color blind individuals, 16(57.14%) were red-green color blind, 5 (17.855) were red color blind, 5 (17.85%) were green color blind and 2 (7.14%) were blue color blind. Furthermore, consanguinity of parents was recorded and interestingly all affected individual parents had consanguineous marriages. Two different types of pedigree analysis were recorded too. In the collected data, people aged between 18 to 60 years were present.Conclusion: We found a significant prevalence of CVD in males (6.3%) than in females (3.5%). The study is significant in that it reported the prevalence of color blindness for the first time in Southern KP, Pakistan. This study provides the foundational understanding of CVD and its prevalence in district Karak and a framework for further research and prevention strategies regarding CVD.